Termination w.r.t. Q of the following Term Rewriting System could be disproven:
Q restricted rewrite system:
The TRS R consists of the following rules:
f(X, g(X), Y) → f(Y, Y, Y)
g(b) → c
b → c
Q is empty.
↳ QTRS
↳ DependencyPairsProof
Q restricted rewrite system:
The TRS R consists of the following rules:
f(X, g(X), Y) → f(Y, Y, Y)
g(b) → c
b → c
Q is empty.
Using Dependency Pairs [1,15] we result in the following initial DP problem:
Q DP problem:
The TRS P consists of the following rules:
F(X, g(X), Y) → F(Y, Y, Y)
The TRS R consists of the following rules:
f(X, g(X), Y) → f(Y, Y, Y)
g(b) → c
b → c
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ ForwardInstantiation
Q DP problem:
The TRS P consists of the following rules:
F(X, g(X), Y) → F(Y, Y, Y)
The TRS R consists of the following rules:
f(X, g(X), Y) → f(Y, Y, Y)
g(b) → c
b → c
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By forward instantiating [14] the rule F(X, g(X), Y) → F(Y, Y, Y) we obtained the following new rules:
F(x0, g(x0), g(y_1)) → F(g(y_1), g(y_1), g(y_1))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ NonTerminationProof
Q DP problem:
The TRS P consists of the following rules:
F(x0, g(x0), g(y_1)) → F(g(y_1), g(y_1), g(y_1))
The TRS R consists of the following rules:
f(X, g(X), Y) → f(Y, Y, Y)
g(b) → c
b → c
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
We used the non-termination processor [17] to show that the DP problem is infinite.
Found a loop by narrowing to the left:
The TRS P consists of the following rules:
F(x0, g(x0), g(y_1)) → F(g(y_1), g(y_1), g(y_1))
The TRS R consists of the following rules:
f(X, g(X), Y) → f(Y, Y, Y)
g(b) → c
b → c
s = F(g(b), g(b), g(y_1)) evaluates to t =F(g(y_1), g(y_1), g(y_1))
Thus s starts an infinite chain as s semiunifies with t with the following substitutions:
- Semiunifier: [y_1 / b]
- Matcher: [ ]
Rewriting sequence
F(g(b), g(b), g(b)) → F(g(b), g(c), g(b))
with rule b → c at position [1,0] and matcher [ ]
F(g(b), g(c), g(b)) → F(c, g(c), g(b))
with rule g(b) → c at position [0] and matcher [ ]
F(c, g(c), g(b)) → F(g(b), g(b), g(b))
with rule F(x0, g(x0), g(y_1)) → F(g(y_1), g(y_1), g(y_1))
Now applying the matcher to the start term leads to a term which is equal to the last term in the rewriting sequence
All these steps are and every following step will be a correct step w.r.t to Q.